The structure of nutrition of Russian students as a risk factor for the development of nutritional diseases - E. V. Kruglikova; E. A. Chanchaeva; R. I. Aizman (Acta Biomedica Scientifica, 2021)
The paper analyzes the literature data on the peculiarities of nutrition of students studying in higher educational institutions of various regions of Russia, and the risks of developing food-related diseases. They are largely associated with the adaptation of students to study at a university, the lack of self-organization skills and a lack of  knowledge in matters of rational nutrition. The actual nutrition of  students, on the one hand, is characterized by a lack of macronutrients and micronutrients intake, on the other hand, by excessive consumption of substances that contribute to the development of obesity. The results of numerous studies show a general pattern of unbalanced nutrition of students in terms of the ratio of saturated and polyunsaturated fatty acids, insufficient consumption of dietary fiber, full-fledged proteins, and  excessive intake of simple carbohydrates. Dietary fiber deficiency can  lead to changes in the composition of the microbiocenosis of the digestive tract, a deficiency of omega-3 fatty acids, and consequently, the imbalance of fatty acid composition of the blood cell membrane. 20–40 % of Russian students show signs of severe hypovitaminosis, especially calciferol, which is caused not only by its deficiency in the diet, but also by physical, geographical, climatic and seasonal factors. The analysis of the content of the main minerals in students shows a sufficient content of calcium in the body, an excess of sodium and a lack of magnesium, potassium and  iron, which is due to both the composition of the food consumed and the peculiarities of the accumulation and excretion of these ions. An analysis of the actual nutrition of students shows the need for counseling young people, especially in the first years of study. The introduction of an educational program on optimal nutrition is possible through the practice of curatorial work during the adaptation of the first-year students to student’s life.